Computer Aided Verification 24th International Conference, CAV 2012, Berkeley, CA, USA, July 7-13, 2012 Proceedings - Madhusudan, P.; Seshia, Sanjit A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 24th International Conference on Computer Aided Verification, CAV 2012, held in Berkeley, CA, USA in July 2012. The 38 regular and 20 tool papers presented were carefully reviewed and selected from 185 submissions. The papers are organized in topical sections on automata and synthesis, inductive inference and termination, abstraction, concurrency and software verification, biology and probabilistic systems, embedded and control systems, SAT/SMT solving and SMT-based verification, timed and hybrid systems, hardware verification, security, verification and synthesis, and tool demonstration.
Keywords: Computer science; Computer hardware; Software engineering; Logic design; Artificial intelligence; Computer Science; Logics and Meanings of Programs; Software Engineering; Mathematical Logic and Formal Languages; Artificial Intelligence (incl. Robotics).; Special Purpose and Application-Based Systems; Computer Hardware